2019
DOI: 10.1016/j.addbeh.2018.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in subjective stress and neuroendocrine response to a stress task among individuals with opioid dependence: A pilot study

Abstract: Background-Opioid dependence is a significant public health problem in the United States and the number of opioid overdose deaths among women has increased dramatically in comparison to men in the last few years. In this context, understanding the biological mechanisms underlying gender differences in vulnerability to opioid dependence is essential. Methods-The current pilot study examined gender differences in subjective stress, heart rate (HR), and cortisol/ dephydroepiandrosterone (DHEA) response to a labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…This exploratory analysis examined if the relation between ACE and oxytocin administration differentially predicted neuroendocrine stress responses for male and female smokers. In line with findings from past studies (Gilmore et al, 2019;Liu et al, 2017), our results suggest that males demonstrated higher post-TSST cortisol levels than females. Further, greater ACE were related to reduced neuroendocrine reactivity in female smokers and increased reactivity in male smokers, consistent with our hypotheses and prior literature (Back et al, 2008;Flanagan et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…This exploratory analysis examined if the relation between ACE and oxytocin administration differentially predicted neuroendocrine stress responses for male and female smokers. In line with findings from past studies (Gilmore et al, 2019;Liu et al, 2017), our results suggest that males demonstrated higher post-TSST cortisol levels than females. Further, greater ACE were related to reduced neuroendocrine reactivity in female smokers and increased reactivity in male smokers, consistent with our hypotheses and prior literature (Back et al, 2008;Flanagan et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Blunted cortisol response to a stress task is also found among individuals with posttraumatic stress disorder and traumatic event exposure (Carpenter et al, 2011; Wichmann et al, 2017). Further, there is preliminary evidence that women with PO use disorder have a blunted cortisol response to a stress task compared to men with PO use disorder (Gilmore et al, under review). Taken together, it may be that PO use combined with prior SA may compound blunted cortisol stress response, thus increasing risk of suicidal ideation and even potentially suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that there are biologically-based sex differences at every stage of drug addiction in both humans and laboratory animals [14][15][16]. Sex differences in the developmental origin and expression of the nervous system may lead to sex differences in addictive behaviours.…”
Section: Biological Aspectsmentioning
confidence: 99%
“…Although there is evidence that many qualitative aspects of the addiction stage do not differ significantly between men and women [16]. However, according to multiple studies, the biology of pain and opioid addiction is different in women and men [14,15]. Focusing on both similarities and differences between men and women in the biological aspects in addiction progress will improve the feasibility of prevention and treatment of addiction disorders.…”
Section: Biological Aspectsmentioning
confidence: 99%